Implementasi Pengadilan Adat Dan Pengadilan Umum Terhadap Tindak Pidana Asusila Lokika Sanggraha - I Dewa Gede Teguh Artawan; Ika Dewi Sartika Saimima; Gatot Efrianto (Jurnal Hukum Sasana, 2022)
In the Balinese Customary Law, there are types of traditional offenses relating to decency, one of which is the offense of lokika sanggraha which is a customary rule that is fundamental in society, constituting a limitation on sexual life. In this customary regulation the act of promiscuity between young men and women, even though it is done with the reason of mutual love and love. In general, any violation of customary law, both civil and criminal, will be resolved by local settlers. The formulation of the problem regarding the implementation of enforcement of immoral acts of lokika sanggraha in traditional courts and general courts and the constraints of enforcement of the immoral crime of lokika sanggraha in traditional courts and general courts. This research, using the method of normative legal research (literature) is supported by interviewees to get the results of the analysis that the implementation of the enforcement of immoral acts of lokika sanggraha in traditional court has not paid attention to the victims of immoral acts and for the general court by applying Article 359 of the Adi Gama Book jo. Article 5 paragraph (3) letter (b) Emergency Law. No. 1 / Drt / 1951 to be convicted. There are several obstacles in the implementation of law enforcement for the lokika sanggraha criminal act namely there is no specific regulation regarding the conduct of the lokika sanggraha and a lack of public legal awareness and the existence of a culture that considers family disgrace if other communities know that their daughter is pregnant outside marriage. The conclusion in this thesis is that law enforcement has not yet been created against the crime of lokika sanggraha because there are obstacles in law enforcement. Suggestions in this thesis are to the Leaders and Indigenous leaders in Bali if in completing the meeting the Sanggraha can consider women as victims of immoral acts and be able to hold men to account.